Evaluation of the Macros-Sahel Model for the Rainfed Production of Corn (Zea Mays L. Cv Suwan I) - Wan Zain, Rushidah (1993)
There is an urgent need to cultivate grain corn on a large scale in Malaysia to meet the growing demand. Before attempting to do this a thorough evaluation of environmental effects on the growth and yield of the crop has to be undertaken. One way of doing this is by using simulation models. Therefore the main objective of this thesis is to adapt the MACROS (crop growth) model for the simulation of potential and rainfed production of corn cultivar Suwan I. A field experiment was set up at Serdang for the establishment of the crop data for corn cultivar Suwan I. The crop data were partitioning of assimilates to the different organs, specific leaf weight constant and crop development rates. They were then used to adapt the MACROS model for simulating potential yield of corn with the L1D module and subsequently the rainfed yield of the crop, the latter using the SAHEL module for the water balance.